The times they are a-changin’: the path and challenges of music teacher education - Cardoso, Mário (2022)
Despite the conditions of complexity and (in)certainty, this new temporality marked by the dynamism of contemporary society and by globality that is transformed directly into a universal elixir in solving the problems of the educational system, represents a place of opportunity, challenge and, especially, of reflection and reconfiguration of the music teacher education, specifically around the professionalism of teachers and their educational dimensions. It is unmistakable that the contexts (social, cultural and educational) have changed in the last decades. However, how (curricular and pedagogical) practices and music teachers' training deal with the daily challenges in educational contexts? What teachers we are training (profile, knowledge and skills)? We are training music teacher for what kind of school: for yesterday, today or tomorrow? What is the role of music teacher trainers? How should training courses be organized? What should be the main components of training? Based on all these issues, it is essential to discuss the dimensions and formative configurations that contribute to constructing a bold and transformative vision of the contemporary music teacher's professional development and pedagogical practice.